A flux for α-MoO3 crystal growth and a crystal growth method
Patent Information
- Application Number
- CN202510074844.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2045-01-17
AI Technical Summary
目前国内外尚无采用助熔剂法生长α-MoO3晶体的报道
[0035]本发明首次采用助熔剂法进行晶体生长,晶体生长设备为高温熔盐炉,结构简单,安全可靠,操作方便,易于维护,可以在空气气氛下进行晶体生长,对生长环境的要求低。炉盖配备有观察窗口,可以观察晶体生长状况,及时调整生长参数。氧化物是晶体生长中常用的助熔剂。本发明中,引入ZnO和TeO2复合助熔剂,利用多种原料的耦合协同作用,能够有效的降低晶体生长温度,降低生长体系的粘度和挥发度,提高生长体系的稳定性:
Smart Images

Figure CN119877080B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of oxide crystal growth, specifically relating to an α-MoO3 crystal growth flux and a crystal growth method. Background Technology
[0002] Molybdenum trioxide (MoO3) is an important transition metal oxide semiconductor. MoO3 has three common crystal phases: thermodynamically stable orthorhombic α-MoO3, thermodynamically metastable monoclinic β-MoO3, and hexagonal h-MoO3. Among them, α-MoO3 is a layered wide-bandgap semiconductor material (E... g =3.05 eV), the layers are connected by weak van der Waals forces, allowing for thinning through exfoliation, while the internal structure is composed of strong covalent and ionic bonds. The unit cell of monolayer α-MoO3 consists of bilayers approximately 0.7 nm thick, edge-shared [MoO6] octahedra. MoO6 contains three different types of O atoms, including terminal oxygen O. t Double-coordinated asymmetric bridging oxygen O a Tri-coordinated symmetric bridging of oxygen O s The distance between Mo atoms between layers is 1.4 nm, which is the thickness of a single layer of α-MoO3. The planar double-layer staggered edges share MoO6 octahedrons arranged in a Z-shape along the
[001] direction, while the oxygen atom centers are shared along the
[100] direction.
[0003] α-MoO3 possesses high specific surface area and porosity, photochromism, electrochromism, photocatalytic degradation, gas sensitivity, and excellent optical and electrochemical properties. Therefore, α-MoO3 has been widely used in photochromic devices, electrochromic devices, gas sensors, photodetectors, field-effect transistors, electrode materials, catalysts, and other fields.
[0004] Currently, the main methods for preparing α-MoO3 crystals include hydrothermal methods, electron beam evaporation, pulsed laser deposition, chemical vapor deposition, and physical vapor deposition.
[0005] Hydrothermal synthesis produces small crystals with low yields, and the impurities and defects introduced during the synthesis process are unsuitable for applications such as optoelectronic devices. Electron beam evaporation yields polycrystalline α-MoO3 films with poor electrical properties and numerous defects. Pulsed laser deposition requires expensive equipment, demands high vacuum levels, has a demanding process, high energy consumption, and low yields. Chemical vapor deposition (CVD) produces small, low-yield α-MoO3 crystals with poor quality.
[0006] Physical vapor deposition (PVD) is currently the most important growth method for α-MoO3 crystals. In 2018, Zheng et al. used PVD to grow α-MoO3 single crystals. The specific steps were as follows: a 3 cm long quartz tube containing α-MoO3 powder was placed in the heating zone of a tube furnace, and a 12 cm long quartz boat was placed in the cooling zone of the tube furnace. The distance between the quartz tube and the quartz boat was 15 cm, and growth was carried out in an oxygen atmosphere. The heating zone was heated to 850–1050 °C at a heating rate of 25 °C / min and maintained for 30 min. , After the α-MoO3 powder was volatilized at high temperature, it recrystallized and deposited in a quartz boat. Heating was then stopped, and the furnace was immediately opened to cool down. The maximum size of the obtained α-MoO3 crystals was approximately 10 × 3 mm. 2 (Binjie Zheng, Zegao Wang, Yuanfu Chen, et al. Centimeter-sized 2D α-MoO3 single crystal: growth, raman anisotropy, and optoelectronic properties, 2D Materials, 5(2018)045011.). In 2019, Sun et al. used PVD to grow α-MoO3 single crystals under an argon atmosphere, and grew Φ2×20cm crystals containing α-MoO3 powder. 3 The quartz tube placed in the heating zone measures Φ8×20cm. 3 In a tube furnace, the argon carrier gas flow rate was 60 sccm. The heating zone was first heated to 710℃ at a rate of 20℃ / min, then to 750℃ at a rate of 2℃ / min. After growth, the temperature was lowered to room temperature, resulting in α-MoO3 crystals ranging in size from micrometers to millimeters at one end of the quartz tube. The largest crystal size was 8×9×0.1 mm. 3 (Haoliang Sun, Huan Zhang, Xinxin Jing, et al. One-step synthesis of centimeter-size alpha-MoO3 with single crystallinity, Applied Surface Science, 476(2019)789-795.). In 2022, Li et al. used PVD to grow α-MoO3 single crystals in a dual-temperature zone tube furnace. The carrier gas was air at a flow rate of 120 sccm. The α-MoO3 powder was placed in a high-temperature zone of 750℃. After being heated and vaporized, the α-MoO3 powder recrystallized and deposited in a low-temperature zone of 550℃. The largest size of the obtained α-MoO3 crystals was 20 × 5 mm. 2The crystals are too thin to be self-supporting (Wei Li, Qingdong Ou, Xiaodong Wang, et al. Large-sized α-MoO3 layered single crystals for superior NO2gas sensing, Applied Surface Science, 586(2022)152793.).
[0007] However, the tube furnace used in PVD, including heating, gas path, exhaust, and control systems, has a complex structure, is difficult to operate, and requires stringent preparation conditions. The tube furnace in PVD lacks an observation window, essentially operating in a "blind" manner, making it impossible to monitor crystal growth in real time, adjust growth parameters promptly, and guarantee crystal quality. PVD requires heating the α-MoO3 raw material to above 750°C for vaporization, resulting in high energy consumption and cost. To ensure proper crystal growth, inert gases or other carrier gases are required. These carrier gases are expensive and produce waste gases during crystal growth, polluting the environment. Furthermore, the flowing carrier gas carries away unvaporized α-MoO3 powder particles, depositing them in the low-temperature region. This introduces amorphous substances into the grown α-MoO3 crystals, leading to low crystallinity, numerous defects, and poor quality. In addition, the crystallization rate of PVD is too fast, resulting in irregularly shaped, small, and thin α-MoO3 crystals with low utilization, failing to meet device fabrication requirements.
[0008] In summary, PVD is currently the mainstream method for growing α-MoO3 crystals. However, this method involves complex equipment, demanding preparation conditions, high costs, environmental pollution, and produces crystals with irregular shapes, small sizes, thin thicknesses, and poor quality, which cannot meet the needs of practical applications.
[0009] Flux-based methods, also known as high-temperature solution methods, are important crystal growth methods. They involve growing crystals from a molten solution at high temperatures, allowing crystals to grow at temperatures below their melting point. Flux-based methods include spontaneous crystallization and top-seeded crystal methods. Currently, there are no reports, either domestically or internationally, of using flux-based methods to grow α-MoO3 crystals. Summary of the Invention
[0010] To address the shortcomings of existing technologies, the present invention aims to provide a low-cost, rapid, safe, and environmentally friendly method for mass production of centimeter-scale, high-quality α-MoO3 single crystals.
[0011] This invention provides a flux for α-MoO3 crystal growth and a crystal growth method. It is the first time that a flux method has been used to grow α-MoO3 crystals, resulting in high-quality single crystals.
[0012] This invention uses a composite flux for the growth of α-MoO3 crystals, and the flux system is ZnO-TeO2.
[0013] Preferably, the molar ratio of α-MoO3:ZnO:TeO2 is 1:(0.1~2.0):(0.5~6).
[0014] Preferably, the compound ZnO can be ZnF2, ZnCO3, ZnCl2, ZnSO3, ZnSO4, ZnSO4·7H2O, Zn3(PO4)2, Zn(NO3 )2·6H2O, Zn(C2H3O2)2.H2O, Zn(OH)2, Zn(NO3)2, Zn(NO2)2, Zn(ClO)2, Zn(ClO2)2, Zn(BrO2)2, Zn(IO2)2, Zn(C2H3O2)2, Zn(HCO3)2, Zn(ClO3)2, Zn(BrO3)2, Zn(IO3) 2. Replacement of Zn(ClO4)2, Zn(BrO4)2, Zn(IO4)2, Zn3(PO3)2, Zn(H2PO4)2, ZnC2O4 or ZnCr2O7.
[0015] Preferably, the compound TeO2 can be replaced by TeCl4, (NH4)2TeO4 or TeF4.
[0016] This invention also provides a method for growing α-MoO3 crystals, which, if using spontaneous crystallization, includes the following steps:
[0017] (a) Prepare and mix the materials according to the molar ratio of α-MoO3:ZnO:TeO2 of 1:(0.1~2.0):(0.5~6), put them into a crucible, place them in a high-temperature molten salt furnace and heat them to 650~700℃ at a rate of 10~50℃ / h to melt them, so as to obtain the crystal growth raw material.
[0018] (b) Stir at a constant temperature for 24 to 48 hours, remove the stirrer, and cool down to 550 to 600°C at a rate of 1 to 10°C / h. Crystals precipitate on the surface of the high-temperature solution, and the crystallization temperature is determined to be 550 to 600°C.
[0019] (c) Using the crystallization temperature of the high-temperature solution as the starting temperature for cooling, the temperature is slowly reduced at a rate of 0.5 to 5 °C / day to allow the crystals to grow.
[0020] (d) After the crystal grows to the required size, use a platinum scooping net to remove the crystal from the liquid surface and cool it to room temperature at a rate of 5-20℃ / h to obtain α-MoO3 crystal; or slowly pour out the high-temperature solution in the crucible to obtain α-MoO3 crystal.
[0021] Preferably, in step (a), a platinum crucible is used to hold the uniformly mixed raw materials.
[0022] Preferably, the stirrer in step (b) is a platinum stirring paddle.
[0023] This invention also provides a method for growing α-MoO3 crystals, which, if using the top seed method, includes the following steps:
[0024] (a) Prepare and mix the materials according to the molar ratio of α-MoO3:ZnO:TeO2 of 1:(0.1~2.0):(0.5~6), put them into a crucible, place them in a high-temperature molten salt furnace and heat them to 650~700℃ at a rate of 10~50℃ / h to melt them, so as to obtain the crystal growth raw material.
[0025] (b) Stir at a constant temperature for 24–48 h, remove the stirrer, cool to 550–600 °C, select a transparent α-MoO3 single crystal as a seed crystal, fix the seed crystal on the seed crystal rod with platinum wire, and determine the saturation point temperature by trial seed crystal method.
[0026] (c) At 1–3°C above the saturation point temperature, introduce the seed crystal that has been fixed on the seed crystal rod into the liquid surface, keep it at a constant temperature for 30–60 minutes, and then cool it down to the saturation point temperature.
[0027] (d) Using the saturation point temperature as the starting temperature for cooling, the temperature is slowly reduced at a rate of 0.2 to 1 °C / day, while the crystal is rotated at a rate of 5 to 30 rpm to allow the crystal to grow.
[0028] (e) After the crystal grows to the required size, the seed crystal rod is lifted to remove the crystal from the liquid surface and cooled to room temperature at a rate of 5-10℃ / h to obtain α-MoO3 crystal.
[0029] Preferably, in step (a), a platinum crucible is used to hold the uniformly mixed raw materials.
[0030] Preferably, the stirrer in step (b) is a platinum stirring paddle.
[0031] Preferably, the orientation of the seed crystal in step (c) is
[010] ,
[100] , or
[001] .
[0032] Preferably, in step (d), the crystal rotation direction is unidirectional or bidirectional.
[0033] Preferably, in step (d), if the crystal rotation direction is bidirectional, the rotation method is alternating between clockwise and counterclockwise rotation, rotating according to the following cycle: in the first direction, the rotation is accelerated, rotated at a constant speed, decelerated, and stopped in sequence; then in the second direction opposite to the first direction, the rotation is accelerated, rotated at a constant speed, decelerated, and stopped in sequence; in bidirectional rotation, the rotation time in each direction is 1 to 3 minutes, and the interval between bidirectional rotations is 0.1 to 0.5 minutes.
[0034] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0035] This invention is the first to employ a flux-based method for crystal growth. The crystal growth equipment is a high-temperature molten salt furnace, which is simple in structure, safe and reliable, easy to operate and maintain, and can perform crystal growth in an air atmosphere with low requirements for the growth environment. The furnace lid is equipped with an observation window to monitor the crystal growth status and adjust growth parameters in a timely manner. Oxides are commonly used fluxes in crystal growth. In this invention, a composite flux of ZnO and TeO2 is introduced. By utilizing the synergistic effect of multiple raw materials, the crystal growth temperature can be effectively reduced, the viscosity and volatility of the growth system can be decreased, and the stability of the growth system can be improved.
[0036] (1) Compared with the PVD method, the flux method can effectively reduce the crystal growth temperature, which is between 550 and 600℃, thus reducing energy consumption and crystal growth difficulty.
[0037] (2) The crystal growth temperature is relatively low, and the high-temperature solution is clear and transparent. The crystal morphology and quality can be observed in real time by visual inspection, and growth parameters such as cooling rate and rotation speed can be optimized in a timely manner to obtain high-quality single crystals.
[0038] (3) The crystal growth temperature is lower, the volatility of the system is lower, and there are fewer volatiles, which can prevent volatiles from falling into the liquid surface and forming impurities, thus improving the stability of the growth system and increasing the success rate of crystal growth.
[0039] (4) In the flux method, under the dual action of high temperature and flux, the viscosity of the solution can be significantly reduced, which is conducive to the transport of melt and heat, increases the crystal growth rate, and reduces the generation of crystal defects such as inclusions and dislocations.
[0040] (5) In the flux method, when the spontaneous crystallization method is used, there are multiple nucleation points on the liquid surface, and multiple blocky transparent crystals will precipitate. These crystals gradually grow and can support themselves, which improves the yield.
[0041] (6) In the flux method, the crystallization region and cooling range of the crystal are large, and a series of regular-shaped, centimeter-sized, thick, high-quality α-MoO3 crystals can be repeatedly and stably grown, which significantly improves the preparation efficiency.
[0042] (7) The large-size, high-quality α-MoO3 crystals prepared by this invention have broad application prospects in the fields of photocatalysis, electrode materials, photodetectors, gas sensors, and field-effect transistors. Attached Figure Description
[0043] Figure 1 This is a photograph of the large-sized α-MoO3 crystals prepared in Example 1.
[0044] Figure 2 This is a photograph of the large-size α-MoO3 crystal prepared in Example 2 after cutting and processing.
[0045] Figure 3 This is the powder X-ray diffraction pattern of the α-MoO3 crystal prepared in Example 2.
[0046] Figure 4 This is the single-crystal X-ray diffraction pattern of the α-MoO3 crystal prepared in Example 2.
[0047] Figure 5 This is the transmission spectrum of the α-MoO3 crystal prepared in Example 2.
[0048] Figure 6 This is the single-crystal rocking curve test spectrum of the α-MoO3 crystal prepared in Example 2. Detailed Implementation
[0049] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the invention.
[0050] Example 1
[0051] α-MoO3 crystals were grown using a spontaneous crystallization method: 143.96 g of α-MoO3, 24.41 g of ZnO, and 207.48 g of TeO2 were ground and uniformly mixed in an agate mortar, and then placed into a Φ60×60 mm mortar. 3 The platinum crucible was placed in a single-stage high-temperature molten salt furnace heated by resistance wire. The platinum crucible was aligned, ensuring its center coincided with the center of the crystal furnace. A platinum stirring paddle was attached, the furnace lid was closed, and the observation hole on the lid was covered with quartz glass. The temperature was increased to 650℃ at a rate of 40℃ / h to completely melt the raw material. The mixture was stirred at this constant temperature for 36 hours until the high-temperature solution was fully homogenized, at which point the stirring paddle was removed. The temperature was then decreased at a rate of 6℃ / h until crystals precipitated on the surface, and the crystallization temperature was determined to be 563℃. Using the crystallization temperature of the high-temperature solution as the starting temperature for cooling, the temperature was slowly decreased at a rate of 0.5–5℃ / day to allow the crystals to grow. After 36 days of crystal growth, the crucible was removed directly, and the high-temperature solution was slowly poured out. A large number of α-MoO3 crystals remained in the crucible, with the largest reaching Φ30×12×0.8mm. 3The crystals are regular in shape and transparent inside.
[0052] Example 2
[0053] α-MoO3 crystals were grown using the top crystallization method: 143.96 g of α-MoO3, 24.41 g of ZnO, and 207.48 g of TeO2 were ground and uniformly mixed in an agate mortar, and then packed into a Φ80×80 mm mortar. 3 Place the platinum crucible into a three-stage high-temperature molten salt furnace heated by resistance wire. Align the platinum crucible, ensuring the center of the crucible coincides with the center of the crystal furnace. Attach a platinum stirring paddle, cover the furnace lid, and seal the observation hole on the lid with quartz glass. Increase the temperature to 680℃ at a rate of 25℃ / h to completely melt the raw material. Stir at this temperature for 24 hours until the high-temperature solution is fully homogeneous, then remove the stirring paddle. Cool to 550–600℃, fix the seed crystal to the seed crystal rod with platinum wire, and determine the saturation point temperature using a trial seed crystal method. The saturation point temperature is 565℃. Increase the temperature to 1℃ above the saturation point temperature, select a transparent α-MoO3 single crystal (
[010] ) as the seed crystal, introduce the seed crystal fixed on the seed crystal rod to the liquid surface, maintain the temperature for 30 minutes, and then cool to the saturation point temperature. The saturation point temperature was used as the starting temperature for cooling, and the temperature was lowered at a rate of 0.2–1 °C / day, while the crystal was rotated at a rate of 5–30 rpm to promote crystal growth. After 30 days of crystal growth, the seed crystal rod was raised to detach the crystal from the liquid surface, and the temperature was lowered to room temperature at a rate of 5 °C / h, yielding a crystal with dimensions of Φ43×12×0.6 mm. 3 α-MoO3 single crystals. The crystals are regular in shape and transparent inside.
[0054] Example 3
[0055] α-MoO3 crystals were grown using a spontaneous crystallization method: 143.96 g of α-MoO3, 40.69 g of ZnO, and 239.40 g of TeO2 were ground and uniformly mixed in an agate mortar, and then placed into a Φ60×60 mm mortar. 3 A platinum crucible was placed in a single-stage high-temperature molten salt furnace heated by resistance wire. The platinum crucible was aligned, ensuring its center coincided with the center of the crystal furnace. A platinum stirring paddle was attached, the furnace lid was closed, and the observation hole on the lid was covered with quartz glass. The temperature was increased to 700℃ at a rate of 35℃ / h to completely melt the raw material. The mixture was stirred at this constant temperature for 48 hours until the high-temperature solution was fully homogenized, at which point the stirring paddle was removed. The temperature was then decreased at a rate of 5℃ / h until crystals precipitated on the surface, and the crystallization temperature was determined to be 556℃. Using the crystallization temperature of the high-temperature solution as the starting temperature for cooling, the temperature was slowly decreased at a rate of 0.5–5℃ / day to allow the crystals to grow. After 12 days of crystal growth, the crystals were retrieved from the liquid surface using a platinum scooping net and cooled to room temperature at a rate of 5℃ / h, yielding a maximum size of Φ8×5×0.3mm. 3α-MoO3 single crystals. The crystals are regular in shape and transparent inside.
[0056] Example 4
[0057] α-MoO3 crystals were grown using a spontaneous crystallization method: 143.96 g of α-MoO3, 81.38 g of ZnO, and 478.79 g of TeO2 were ground and uniformly mixed in an agate mortar, and then placed into a Φ100×100 mm mortar. 3 The platinum crucible was placed in a single-stage high-temperature molten salt furnace heated by resistance wire. The platinum crucible was aligned, ensuring its center coincided with the center of the crystal furnace. A platinum stirring paddle was attached, the furnace lid was closed, and the observation hole on the lid was covered with quartz glass. The temperature was increased to 680℃ at a rate of 40℃ / h to completely melt the raw material. The mixture was stirred at this constant temperature for 48 hours until the high-temperature solution was fully homogenized, at which point the stirring paddle was removed. The temperature was then decreased at a rate of 5℃ / h until crystals precipitated on the surface, determining the crystallization temperature to be 550℃. Using the crystallization temperature of the high-temperature solution as the starting temperature for cooling, the temperature was slowly decreased at a rate of 0.5–5℃ / day to allow the crystals to grow. After 18 days of crystal growth, the crucible was removed directly, and the high-temperature solution was slowly poured out. A large amount of α-MoO3 crystals remained in the crucible, with the largest reaching Φ20×6×0.4mm. 3 The crystals are regular in shape and transparent inside.
[0058] Example 5
[0059] α-MoO3 crystals were grown using a spontaneous crystallization method: 143.96 g of α-MoO3, 122.07 g of ZnO, and 638.39 g of TeO2 were ground and uniformly mixed in an agate mortar, and then placed into a Φ100×100 mm mortar. 3 The platinum crucible was placed in a single-stage high-temperature molten salt furnace heated by resistance wire. The platinum crucible was aligned, ensuring its center coincided with the center of the crystal furnace. A platinum stirring paddle was attached, the furnace lid was closed, and the observation hole on the lid was covered with quartz glass. The temperature was increased to 665℃ at a rate of 25℃ / h to completely melt the raw material. The mixture was stirred at this constant temperature for 36 hours until the high-temperature solution was fully homogenized, at which point the stirring paddle was removed. The temperature was then decreased at a rate of 5℃ / h until crystals precipitated on the surface, and the crystallization temperature was determined to be 552℃. Using the crystallization temperature of the high-temperature solution as the starting temperature for cooling, the temperature was slowly decreased at a rate of 0.5–5℃ / day to allow the crystals to grow. After 33 days of crystal growth, the crystals were retrieved from the liquid surface using a platinum scooping net and cooled to room temperature at a rate of 10℃ / h, yielding a maximum size of Φ35×12×0.4mm. 3 α-MoO3 single crystals. The crystals are regular in shape and transparent inside.
[0060] Example 6
[0061] α-MoO3 crystals were grown using the top crystallization method: 143.96 g of α-MoO3, 162.76 g of ZnO, and 957.59 g of TeO2 were ground and uniformly mixed in an agate mortar, and then placed into a Φ100×100mm mortar. 3 Place the platinum crucible into a three-stage high-temperature molten salt furnace heated by resistance wire. Align the platinum crucible, ensuring the center of the crucible coincides with the center of the crystal furnace. Attach a platinum stirring paddle, cover the furnace lid, and seal the observation hole on the lid with quartz glass. Increase the temperature to 670℃ at a rate of 30℃ / h to completely melt the raw material. Stir at this temperature for 48 hours until the high-temperature solution is fully homogeneous, then remove the stirring paddle. Cool to 550-600℃ and fix the seed crystal onto the seed crystal rod with platinum wire. Determine the saturation point temperature using a trial seed crystal method; the saturation point temperature is 551℃. Increase the temperature to 2℃ above the saturation point temperature, select a transparent α-MoO3 single crystal (
[010] ) as the seed crystal, and introduce the seed crystal, already fixed on the seed crystal rod, to the liquid surface. Maintain the temperature for 40 minutes, then cool to the saturation point temperature. The saturation point temperature was used as the starting temperature for cooling, and the temperature was lowered at a rate of 0.2–1 °C / day, while the crystal was rotated at a rate of 5–30 rpm to promote crystal growth. After 23 days of crystal growth, the seed crystal rod was raised to detach the crystal from the liquid surface, and the temperature was lowered to room temperature at a rate of 10 °C / h, yielding a crystal with dimensions of Φ28×8×0.4 mm. 3 α-MoO3 single crystals. The crystals are regular in shape and transparent inside.
[0062] Example 7
[0063] α-MoO3 crystals were grown using the top crystallization method: 143.96 g of α-MoO3, 8.14 g of ZnO, and 79.80 g of TeO2 were ground and uniformly mixed in an agate mortar, and then packed into a Φ60×60 mm mortar. 3Place the platinum crucible into a single-stage high-temperature molten salt furnace heated by resistance wire. Align the platinum crucible, ensuring the center of the crucible coincides with the center of the crystal furnace. Attach a platinum stirring paddle, cover the furnace lid, and seal the observation hole on the lid with quartz glass. Increase the temperature to 670℃ at a rate of 20℃ / h to completely melt the raw material. Stir at this temperature for 48 hours until the high-temperature solution is fully homogeneous, then remove the stirring paddle. Cool to 550-600℃, fix the seed crystal to the seed crystal rod with platinum wire, and determine the saturation point temperature using a trial seed crystal method. The saturation point temperature is 596℃. Increase the temperature to 1℃ above the saturation point temperature, select a transparent α-MoO3 single crystal (
[001] ) as the seed crystal, introduce the seed crystal fixed on the seed crystal rod to the liquid surface, maintain the temperature for 30 minutes, and then cool to the saturation point temperature. The saturation point temperature was used as the starting temperature for cooling, and the temperature was lowered at a rate of 0.2–1 °C / day, while the crystal was rotated at a rate of 5–30 rpm to promote crystal growth. After 11 days of crystal growth, the seed crystal rod was raised to detach the crystal from the liquid surface, and the temperature was lowered to room temperature at a rate of 5 °C / h, yielding a crystal with dimensions of Φ16×7×0.3 mm. 3 α-MoO3 single crystals. The crystals are regular in shape and transparent inside.
[0064] Example 8
[0065] α-MoO3 crystals were grown using the top crystallization method: 143.96 g of α-MoO3, 16.28 g of ZnO, and 159.60 g of TeO2 were ground and uniformly mixed in an agate mortar, and then packed into a Φ80×80 mm mortar. 3 Place the platinum crucible into a three-stage high-temperature molten salt furnace heated by resistance wire. Align the platinum crucible, ensuring the center of the crucible coincides with the center of the crystal furnace. Attach a platinum stirring paddle, cover the furnace lid, and seal the observation hole on the lid with quartz glass. Increase the temperature to 690℃ at a rate of 30℃ / h to completely melt the raw material. Stir at this temperature for 48 hours until the high-temperature solution is fully homogeneous, then remove the stirring paddle. Cool to 550-600℃ and fix the seed crystal onto the seed crystal rod with platinum wire. Determine the saturation point temperature using a trial seed crystal method; the saturation point temperature is 580℃. Increase the temperature to 2℃ above the saturation point temperature, select a transparent α-MoO3 single crystal (
[010] ) as the seed crystal, and introduce the seed crystal, already fixed on the seed crystal rod, to the liquid surface. Maintain the temperature for 30 minutes, then cool to the saturation point temperature. The saturation point temperature was used as the starting temperature for cooling, and the temperature was lowered at a rate of 0.2–1 °C / day, while the crystal was rotated at a rate of 5–30 rpm to promote crystal growth. After 34 days of crystal growth, the seed crystal rod was raised to detach the crystal from the liquid surface, and the temperature was lowered to room temperature at a rate of 5 °C / h, yielding a crystal with dimensions of Φ39×15×0.5 mm. 3 α-MoO3 single crystals. The crystals are regular in shape and transparent inside.
[0066] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and substitutions can be made without departing from the technical principles of the present invention, and these improvements and substitutions should also be considered within the scope of protection of the present invention.
Claims
1. A flux-based growth method for α-MoO3 crystals, characterized in that, If α-MoO3 crystals are obtained by spontaneous crystallization, the following steps are included: (a) Prepare and mix the materials according to the molar ratio of α-MoO3:ZnO:TeO2 of 1:(0.1~2.0):(0.5~6), put them into a crucible, place them in a high-temperature molten salt furnace and heat them to 650~700℃ at a rate of 10~50℃ / h to melt them, so as to obtain the crystal growth raw material. (b) Stir at a constant temperature for 24–48 h, remove the stirrer, and cool down to 550–600 °C at a rate of 1–10 °C / h. Crystals precipitate on the surface of the high-temperature solution, and the crystallization temperature is determined to be 550–600 °C. (c) Using the crystallization temperature of the high-temperature solution as the starting temperature for cooling, the temperature is slowly reduced at a rate of 0.5 to 5 °C / day to allow the crystals to grow. (d) After the crystal grows to the required size, use a platinum scooping net to remove the crystal from the liquid surface and cool it to room temperature at a rate of 5-20℃ / h to obtain α-MoO3 crystal; or slowly pour out the high-temperature solution in the crucible to obtain α-MoO3 crystal.
2. A flux-based growth method for α-MoO3 crystals, characterized in that, If the top seed crystal method is used to obtain α-MoO3 crystals, the following steps are included: (a) Prepare and mix the materials according to the molar ratio of α-MoO3:ZnO:TeO2 of 1:(0.1~2.0):(0.5~6), put them into a crucible, place them in a high-temperature molten salt furnace and heat them to 650~700℃ at a rate of 10~50℃ / h to melt them, so as to obtain the crystal growth raw material. (b) Stir at a constant temperature for 24–48 h, remove the stirrer, cool to 550–600 °C, select a transparent α-MoO3 single crystal as a seed crystal, fix the seed crystal on the seed crystal rod with platinum wire, and determine the saturation point temperature by trial seed crystal method. (c) At 1–3°C above the saturation point temperature, introduce the seed crystal that has been fixed on the seed crystal rod into the liquid surface, keep it at a constant temperature for 30–60 minutes, and then cool it down to the saturation point temperature. (d) Using the saturation point temperature as the starting temperature for cooling, the temperature is slowly reduced at a rate of 0.2 to 1 °C / day, while the crystal is rotated at a rate of 5 to 30 rpm to allow the crystal to grow. (e) After the crystal grows to the required size, the seed crystal rod is lifted to remove the crystal from the liquid surface and cooled to room temperature at a rate of 5-10℃ / h to obtain α-MoO3 crystal.
3. The growth method according to claim 1 or 2, characterized in that, In step (a), a platinum crucible is used to hold the uniformly mixed raw materials.
4. The growth method according to claim 1 or 2, characterized in that, The agitator in step (b) is a platinum agitator.
5. The growth method according to claim 2, characterized in that, In step (c), the seed crystal is oriented in the direction of [010], [100], or [001].
6. The growth method according to claim 2, characterized in that, In step (d), the crystal rotation direction is either unidirectional or bidirectional.
7. The growth method according to claim 2, characterized in that, In step (d), if the crystal rotation direction is bidirectional, the rotation method is alternating between clockwise and counterclockwise rotation, rotating according to the following cycle: in the first direction, the rotation is accelerated, rotated at a constant speed, decelerated, and stopped in sequence; then in the second direction opposite to the first direction, the rotation is accelerated, rotated at a constant speed, decelerated, and stopped in sequence; in bidirectional rotation, the rotation time in each direction is 1 to 3 minutes, and the interval between bidirectional rotations is 0.1 to 0.5 minutes.
Citation Information
Patent Citations
Compound tellurium-zinc-lead arsenate and tellurium-zinc-lead arsenate nonlinear optical crystal as well as preparation method and application thereof
CN110528080A